Increased Melting Heat Transfer in the Latent Heat Energy Storage from the Tube-and-Shell Model to the Combine-and-Shell Model. (17th September 2017) - Korawan, Agus Dwi; Soeparman, Sudjito; Wijayanti, Widya; Widhiyanuriyawan, Denny
Abstract : The melting of paraffin in thermal storage tube-and-shell and combine-and-shell models was conducted with the numerical research aim of decreasing the charge time through changing the shape of the tube into combining form. The results discussed are temperature contour, liquid-solid interface contour, temperature distribution, liquid fraction, and the average Nusselt number. The results show that the charge time in the tube-and-shell model is 2000 s, while the combine-and-shell model is 1200 s, meaning an overall decrease in charge time in the combine-and-shell model by 40% when compared to that of the tube-and-shell model.